2010
DOI: 10.1016/j.neuroimage.2009.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory activity in prefrontal and posterior regions during implicit letter-location binding

Abstract: Many cognitive abilities involve the integration of information from different modalities, a process referred to as "binding." It remains less clear, however, whether the creation of bound representations occurs in an involuntary manner, and whether the links between the constituent features of an object are symmetrical. We used magnetoencephalography to investigate whether oscillatory brain activity related to binding processes would be observed in conditions in which participants maintain one feature only (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 120 publications
(169 reference statements)
4
42
4
Order By: Relevance
“…This effect was evident in Experiments 1 and 2. In the study by Campo et al (2010), in contrast to our results, spatial and verbal binding occurred when the relevant dimension was verbal (i.e., changes in the location affected recognition of the letter, and changes in the letter did not affect memory of the location). These differences can be explained by the experimental conditions in the studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This effect was evident in Experiments 1 and 2. In the study by Campo et al (2010), in contrast to our results, spatial and verbal binding occurred when the relevant dimension was verbal (i.e., changes in the location affected recognition of the letter, and changes in the letter did not affect memory of the location). These differences can be explained by the experimental conditions in the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…These differences can be explained by the experimental conditions in the studies. In the study by Campo et al (2010), the task required the recognition of just one item. A frame in the stimuli served as a mnemonic resource for the spatial information, and only the responses in the positive trials were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, we examined whether the number of features to be retained during the memory task influences the asymmetry. Indeed, in previous studies showing asymmetric binding, spatial information did not need to be retained (see, e.g., Campo et al, 2010;Jiang et al, 2000). In another study, Maybery et al (2009) showed asymmetric binding with letters as the independent feature when participants had to retain one feature, but symmetric binding when participants had to retain both the verbal and spatial features.…”
Section: Asymmetric Binding In Memorymentioning
confidence: 90%
“…Previous results, therefore, have suggested that binding in visual memory is asymmetric: Object features are bound to their locations, whereas locations-or the spatial configuration of the display as a whole (see Jiang et al, 2000)-can be retained independently (see Campo et al, 2010). This type of asymmetry has not been observed consistently in the literature, however.…”
Section: Asymmetric Binding In Memorymentioning
confidence: 93%
See 1 more Smart Citation